(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article aims to show the life and professional strategies of the dancer, choreographer and above all, Hip Hop artist FlowJack. The text indicates that the practice of the analyzed artist represents ways of evidencing a black cultural artistic project towards decolonization. Furthermore, the article exposes aspects of the Uantpi dance teaching methodology and the Fluxo Mandinga workshop. This proposal, the result of doctoral research, employ writing as a methodology to highlight black epistemes in the field of scientific knowledge and presented Africanities as a way of life of black people imbued with a sense of humanity.